Prospective cohort study comparison of bipolar and monopolar transurethral resection of prostate for benign prostatic hyperplasia: haemoglobin, sodium levels, and urethral catheter traction application - Pradiptha, Nyoman T.; Duarsa, Gede W. K.; Mahadewa, Tjokorda G. B. (International Journal of Research in Medical Sciences, 2019)
Background: Bipolar Transurethral Resection of Prostate (TURP) and monopolar TURP has been widely used for surgical management of bladder outlet obstruction due to benign prostatic hyperplasia. The aim of this study is to prove the difference of haemoglobin (Hb), sodium levels (Na⁺), application of urethral catheter traction between two groups. Methods: Prospective cohort study was conducted for 82 patients as eligible sample which divided into two groups, bipolar TURP and Monopolar TURP from September 2018 to August 2019. The patient’s demographics, preoperative, postoperative data, and application of urethral catheter traction were recorded. Results: The result shows basic characteristic data seem comparable. The decline levels of Hb before surgery 14.2(2.6) and after surgery 13.6(2.6) in monopolar group was significant (p=0.01), and also in bipolar group 13.7(2.1) vs 13.4(2.1) was significant (p=0.033), despite decreasing Hb levels between two groups were insignificant (p=0.639) but decline levels of Na between two groups were significant (p=0.013) Na⁺ level in bipolar 0(3) and monopolar 1(4). The application of urethral catheter traction in bipolar (19.5%) lower than monopolar (80.5%) were statistically significant (p<0.001). Conclusions: Based on the results of this study, bipolar TURP surgery can be an optional recommendation in treating Benign Prostate Hyperplasia (BPH) in terms of better preserving blood sodium during surgery and low use of traction without significant bleeding complications.